Toughening Of Epoxy Resin With Modified Liquid Natural Rubbers And Acrylonitrile-Butadiene Liquid Rubbers [TP1180.E6 A136 2005 f rb]. - Ben Saleh, Abdulali Bashir Ahmed (2005)
The preparation of liquid natural rubber (LNR) by depolymerizing deprotenized natural rubber latex was carried out. Getah asli cecair (LNR) disediakan dengan cara penyahpempolimeran penyahprotinan lateks getah asli ternyahprotin.